Uterine volume measurement as a determinant in route of hysterectomy - Hanifa, Dudekula; Thakkar, Nandita A.; Premalatha, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Objectives of the study were to determine the role of uterine volume rather than uterine length in assessing the route of hysterectomy; to estimate the cut-off of uterine volume for route of hysterectomy; and to correlate uterine volume measured preoperatively by ultrasound with post-operative uterine weight. Methods: This was a prospective observational study including a total of 101 women who underwent hysterectomies (vaginal, laparascopic assisted vaginal hysterectomy (LAVH), total laparascopic hysterectomy (TLH), abdominal) in a period of 2 years 2 months from July 2018 to August 2020 in Mehta Multispeciality Hospital, Chetpet, Chennai. Uterine size was measured by clinical examination. Ease of the procedure with various uterine volume and routes of hysterectomy were studied. Results: 51 (50.49%) underwent vaginal route (including laparascopic hysterectomy), 50 (49.50%) underwent abdominal hysterectomy. Mean uterine volume leading to removal vaginally was 168.09±139.28 cc whereas 309.12±182.47 cc for abdominal hysterectomy (p=0.001) which was statistically significant. vaginal hysterectomy was done without difficulty up to 300 cc. Postoperative complications were less with vaginal hysterectomy compared to abdominal hysterectomy was statistically significant (p=0.0001).Uterine volume measured pre operatively by ultrasound showed positive correlation (r=0.82) with post-operative uterine weight proved that uterine volume measurements was superior to the clinical estimate of uterine size in assessing the route of hysterectomy. Conclusions: Uterine volume on ultrasonography (USG) can be a good predictor in deciding whether hysterectomy via vaginal route is possible.